System concept for association and positioning of vehicles using SAW RFID tags - Caldero Bardaji, Pau; Zoeke, Dominik (EuRAD 2019 - 2019 16th European Radar Conference, 2019)
In this work we propose a system concept for simultaneous wireless identication and positioning of vehicles using SAW (surface acoustic wave) RFID (radio frequency identication) tags. Multichannel interrogation allows for additional extraction of vehicle orientation as well as resolution of ambiguities. The system is optimized for low-latency parallel interrogation with a measurement rate of 10 kHz to enable an accurate, real-time and unambiguous positioning with high statistical robustness, even for high-speed vehicles. Feasibility is demonstrated based on real experiments with tags mounted on an electronically controlled moving platform, showing its potential for localization and orientation measurements.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Localization; Mobility; RFID; SAW